Functional traits variation of the tree component in response to edaphic gradients in a cloud forest in the south of Brazil Variação de atributos funcionais do componente arbóreo em função de gradientes edáficos em uma floresta nebular no sul do Brasil - Soboleski V.F.* (2017)
We aimed to investigate how the environmental heterogeneity affects the spatial variation of functional diversity and functional traits of a tree community in a cloud forest in the South of Brazil. For this, we selected the 19 most abundant species identified in a forest fragment survey. The study environmental variables were obtained from a previous study conducted in the same area. For each species, we measured the wood density, leaf area, specific leaf area and maximum potential height. We also determined the dispersal syndromes and deciduousness. We determined the community weighted mean for all traits and the functional diversity. The environmental data were ordered by Principal Component Analysis and Linear Models were fitted relating the significant Principal Components and the values of functional traits and of functional diversity. Whereas sites with higher fertility soils favored species with acquisitive strategies (i.e lower wood density and greater leaf area), and showed a higher functional diversity; lower fertility soils sites favored conservative strategies (i.e higher wood density and smaller leaf area), and had a lower functional diversity. We conclude that the studied forest showed habitat partitioning by species with different ecological strategies, in function of edaphic variations.